2022
DOI: 10.3346/jkms.2022.37.e140
|View full text |Cite
|
Sign up to set email alerts
|

Croup as a Manifestation of SARS-CoV-2 Omicron Variant Infection in Young Children

Abstract: Croup is an acute upper respiratory disease primarily caused by the parainfluenza virus. Owing to inflammation and edema of the upper airways, children present with barky cough and stridor, and some may experience respiratory distress. We investigated children aged < 5 years with coronavirus disease 2019 (COVID-19) admitted to two hospitals in Seoul, South Korea, and observed a spike in croup cases during the omicron surge. Among the 569 children admitted from March 1, 2021 to February 25, 2022, 21 children (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…But no patients required invasive ventilation or died. 9 18 In three retrospective studies, the COVID-19 variant and the omicron subtype were not identified. 9 17 18 However, in our cases, a COVID-19 variant analysis was performed, and omicron sublineage BA.2 variants (Stealth omicron) were identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But no patients required invasive ventilation or died. 9 18 In three retrospective studies, the COVID-19 variant and the omicron subtype were not identified. 9 17 18 However, in our cases, a COVID-19 variant analysis was performed, and omicron sublineage BA.2 variants (Stealth omicron) were identified.…”
Section: Discussionmentioning
confidence: 99%
“… 9 18 In three retrospective studies, the COVID-19 variant and the omicron subtype were not identified. 9 17 18 However, in our cases, a COVID-19 variant analysis was performed, and omicron sublineage BA.2 variants (Stealth omicron) were identified. Lyngse et al 10 found that BA.2 was substantially more transmissible than BA.1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Likewise, increasing cases of croup, an acute laryngotracheobronchitis characterized by barking cough, were noted in South Korea, during the Omicron surge. 15 What is more, the endocytic entry which Omicron prefer over angiotensin-converting enzyme 2 (ACE2) dependent pathway, could also explain the higher number of pediatric cases since children have a lower number of ACE receptors. 16,17 An experimental study compared the replication competence of wild type, pre-Delta variants (D614G, Alpha and Beta), Delta, and Omicron in human bronchi and lungs.…”
mentioning
confidence: 99%